Penerapan Pembentukan Website Untuk Meningkatkan Kualitas Pelayanan Publik Sebagai Wujud Innovative Governance (Studi Pada Dinas Komunikasi dan Informatika Kota Malang) - Fitria Ahmad Rizkil Aziz (Jurnal Administrasi Publik, 2015)
Abstract: Implementation Establishment Website To Improve the Quality of Public Services As Being Innovative Governance. One of the needs of the community that is public information. So that these needs are met, the government makes the innovation that is making the government's official website, which is included in the E-Government policy. This study uses descriptive qualitative approach. The technique of collecting data through observation, documentation, and interviews with all employees staff the Office of Communications and Information Technology as well as with some of Malang Malang community who use the internet as well as ever accessing the site www.malangkota.go.id website. Based on the results of research conducted shows that the official website of Malang was formed based on the needs of the community will be public information. In addition, the application of this website have an impact on improving the quality of public services. Actor initiators of the website Malang is the Tourism Office of Information and Communications in particular sub-field data collection. Application of this website can not be separated from the role of stakeholders in the government, private, and community participation so that the application of this website can be accomplished in accordance objectives and functions. But in applicability, the data provided in the website is less updates.Â  Keywords: website, public service, innovative governance Abstrak: Penerapan Pembentukan Website Untuk Meningkatkan Kualitas Pelayanan Publik Sebagai Wujud Innovative Governance. Salah satu kebutuhan masyarakat yaitu informasi publik. Agar kebutuhan tersebut terpenuhi, pemerintah membuat inovasi yaitu pembuatan website resmi pemerintah, yang masuk dalam kebijakan E-Government. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data melalui observasi, dokumentasi, dan wawancara dengan segenap staf pegawai Dinas Komunikasi dan Informatika Kota Malang serta dengan beberapa masyarakat Kota Malang yang menggunakan internet serta pernah mengakses situs website www.malangkota.go.id. Berdasarkan hasil penelitian yang dilakukan menunjukkan bahwa website resmi Kota Malang dibentuk berdasarkan kebutuhan masyarakat akan informasi publik. Selain itu penerapan website ini berdampak pada peningkatan kualitas pelayanan publik. Aktor penggagas website Kota Malang adalah Dinas Pariwisata Informasi dan Komunikasi khususnya sub bidang pendataan. Penerapan website ini tidak terlepas dari peran stakeholder yakni pemerintah, swasta, dan masyarakat yang ikut berpartisipasi sehingga penerapan website ini dapat terlaksana sesuai tujuan dan fungsinya. Namun dalam penerapanya, data yang tersedia dalam website kurang update. Â  Kata kunci: website, pelayanan publik, innovative governance